The effect of 808 nm and 905 nm wavelength light on recovery after spinal cord injury - Svobodova, Barbora; Kloudova, Anna; Ruzicka, Jiri; Kajtmanova, Ludmila; Navratil, Leos; Sedlacek, Radek; Suchy, Tomas; Jhanwar-Uniyal, Meena; Jendelova, Pavla; Machova Urdzikova, Lucia (Scientific reports, 2019)
We investigated the effect of a Multiwave Locked System laser (with a simultaneous 808 nm continuous emission and 905 nm pulse emission) on the spinal cord after spinal cord injury (SCI) in rats. The functional recovery was measured by locomotor tests (BBB, Beam walking, MotoRater) and a sensitivity test (Plantar test). The locomotor tests showed a significant improvement of the locomotor functions of the rats after laser treatment from the first week following lesioning, compared to the controls. The laser treatment significantly diminished thermal hyperalgesia after SCI as measured by the Plantar test. The atrophy of the soleus muscle was reduced in the laser treated rats. The histopathological investigation showed a positive effect of the laser therapy on white and gray matter sparing. Our data suggests an upregulation of M2 macrophages in laser treated animals by the increasing number of double labeled CD68+/CD206+ cells in the cranial and central parts of the lesion, compared to the control animals. A shift in microglial/macrophage polarization was confirmed by gene expression analysis by significant mRNA downregulation of Cd86 (marker of inflammatory M1), and non-significant upregulation of Arg1 (marker of M2). These results demonstrated that the combination of 808 nm and 905 nm wavelength light is a promising non-invasive therapy for improving functional recovery and tissue sparing after SCI.
Keywords: laserová terapie s nízkou intenzitou světla; krysa rodu Rattus; mužské pohlaví; Locomotion; Male; lektiny vázající mannosu; Low-Level Light Therapy; lektiny typu C; Spinal Cord Regeneration; Lectins, C-Type; receptor mannózy; antigeny CD86; Antigens, CD; mícha; Rats; receptory buněčného povrchu; regenerace míchy; poranění míchy; potkani Wistar; CD antigeny; lokomoce; Mannose Receptor; Animals; Spinal Cord Injuries; zvířata; B7-2 Antigen; antigeny diferenciační myelomonocytární; Rats, Wistar; Receptors, Cell Surface; Antigens, Differentiation, Myelomonocytic; Mannose-Binding Lectins; Spinal Cord